TGR5, GLP-1, and GIP expression in diabetic Wistar rats in response to Ficus exasperata vahl leaf extract - Olorunsola Israel Adeyomoye; Juliana Bunmi Adetunji; Olugbemi Temitope Olaniyan; Charles Oluwaseun Adetunji; Doris Yinka Oluwafemi (Elsevier, 2024)
Background: Diabetes mellitus remains a critical global health issue, driving the need for continual exploration of new therapeutic strategies. Ficus exasperata Vahl, renowned for its extensive ethnomedicinal use, holds promise as a potential remedy for diabetes. However, its precise mechanisms of action in managing diabetes remain unclear. This study aimed to investigate the impact of Ficus exasperata Vahl leaf extract (MEFE) on the expression of TGR5, GLP-1, and GIP in diabetic Wistar rats. Method: Using methanol extraction, Ficus exasperata was processed and characterized through GC-MS analysis. Twenty rats were divided into four groups: diabetic untreated, normal control, diabetes treated with MEFE (200 mg/kg), and diabetes treated with insulin (0.3 units). Diabetes induction utilized alloxan monohydrate (150 mg/kg, intraperitoneal), followed by daily treatments for 28 days. Blood glucose and insulin levels were assessed via glucose oxidase and ELISA, while antioxidant enzyme activities (SOD, catalase, GPx) and total protein were measured using randox kits. Gene expression of GLP-1, TGR5, and GIP was quantified through qPCR. In silico docking of MEFE compounds to the P2Y1 receptor was conducted using Cavity-detection guided blind-docking software. Pancreatic islet histology was examined with hematoxylin and eosin stains, and statistical significance was determined with GraphPad Prism (p < 0.05). Result: The GC-MS analysis identified 23 constituents in MEFE, with kaur-16-ene exhibiting the highest binding affinity (-8.2 Kcal) against the P2Y1 receptor. Significant reductions in blood glucose levels were observed in the MEFE-treated diabetic group, accompanied by increased expression of insulin, TGR5, GLP-1, GIP, SOD, catalase, and GPx compared to the untreated diabetic group. Additionally, MEFE treatment facilitated the regeneration of pancreatic islet cells. Conclusion: These findings suggest that MEFE exerts antioxidative effects and stimulates genes crucial for controlling blood glucose levels in diabetic rats.